Prevalence of MRSA nasal colonization among community members and healthcare workers at private and public hospitals in Khartoum State, Sudan. - ha Abu Algasim Elrayah,1 Luai Marouf ¹Mohammed BabikerIdris, 1* SlmaZainElabde en Mustafa,1 Maryam Abdalla Mohammed,1Ma (Journal of Biomedical and Pharmaceutical Research, 2017)
Background:MRSA is a growing public health threat around the world. Until now, we are still unable to control the spread of staphylococcal infection and the development of resistance. Objectives: To determine the prevalence of MRSA nasal colonization and its antimicrobial susceptibility profile colonization among community members and healthcare workers at four private and public hospitals in Khartoum State, capital city of Sudan. Materials and methods: A total of three hundred and seven nasal swabs were collected during March to April 2017. Isolates were identified using conventional laboratory assays. Kirby–Bauer disk diffusion method was used for antibiotic susceptibility testing and methicillin resistance was confirmed using Oxacillin disks. Results: Of the 70 S.aureus isolated, 80% represented MRSA. The occurrence of MRSA was significantly higher among healthcare worker than community individuals [51.42% (36/70) vs. 28.57% (20/70)] (p=0.008). The overall resistance rates to commonly prescribed antibiotics in isolates were low with slightly high percentage of intermediate strains. Tetracycline was the least effective agents for hospital infections of S.aureus with sensitivity being 55%. Conclusion: The observed pattern of susceptibility showed those medical care workers were colonized with more antibiotics-resistant S.aureus isolates than community members. Of greater significance is the finding that all community isolates were MRSA strains which indicates a growing urgency to study the colonization behavior of CA-MRSA in Sudan in order to create plausible strategies for controlling this potential pathogen. Keywords:MRSA, S.aureus, nasal carriage, Antimicrobial susceptibility